High levels of acetoacetate and glucose increase expression of cytokines in bovine hepatocytes, through activation of the NF-κB signalling pathway. Issue 1 (12th February 2016) - Li, Yu; Ding, Hongyan; Wang, Xichun; Liu, Lei; Huang, Dan; Zhang, Renhe; Guo, Lihui; Wang, Zhe; Li, Xiaobing; Liu, Guowen; Wu, Jinjie; Li, Xinwei
Abstract : Elevated levels of blood interleukin-1β (IL-1β), interleukin-6 (IL-6) and tumour necrosis factor–α (TNF–α) increase insulin resistance and result in inflammation. It is not clear whether elevated blood level of acetoacetate (ACAC) and decreased blood level of glucose, which are the predominant characteristics of clinical biochemistry in ketotic dairy cows, increase proinflammatory cytokines and subsequent inflammation. The objective of this study was to test the hypothesis that ACAC and glucose activate the NF-κB signalling pathway to regulate cytokines expression in bovine hepatocytes. Bovine hepatocytes were cultured with ACAC (0–4·8 mm ) and glucose (0–5·55 mm ) with or without NF-κB inhibitor PDTC for 24 h. The secretion and mRNA levels of cytokines were determined by enzyme-linked immunosorbent assay (ELISA) and real-time fluorescence quantitative polymerase chain reaction (qRT-PCR). The NF-κB signalling pathway activation was evaluated by western blotting. Results showed that the secretion and expression of IL-1β, IL-6 and TNF-α increased in an ACAC dose-dependent manner. Additionally, there was an increase in the secretion and mRNA expression of these three cytokines in glucose treatment group, which increased significantly when the glucose concentrations exceed 3·33 mm . Furthermore, both ACAC and glucose upregulated NF-κB p65 protein expression and IκBα phosphorylation levels. However, these effects were reduced by PDTC. These results demonstrate that elevated levels of ACAC and glucose increase the synthesis and expression of proinflammatory factors by activating NF-κB signalling pathway in hepatocytes, which may contribute to inflammation injury in ketotic dairy cows.